Analysis of Women’s Knowledge, Health Risk Perceptions, Beliefs and Avoidance Behaviour in Relation to Endocrine-Disrupting Chemicals in Personal Care and Household Products - Adrianna Trifunovski; Nooshin Khobzi Rotondi; Jennifer Abbass-Dick; Caroline Barakat (Toxics)
Evidence highlights the association between endocrine-disrupting chemicals (EDCs) found in personal care and household products (PCHPs) and adverse reproductive and developmental health outcomes. Women are disproportionately at risk due to frequent use of PCHPs, encountering a variety of different chemicals daily. Despite known health risks, existing policies often fail to provide adequate protection, with gaps remaining in understanding women’s knowledge, risk perceptions, and beliefs about EDCSs in PCHP, as well as how these influence avoidance behaviours. This study examines women’s knowledge, health risk perceptions, beliefs, and avoidance behaviors regarding EDCs commonly found in PCHPs, including bisphenol A, lead, parabens, phthalates, perchloroethylene, and triclosan. Guided by the Health Belief Model, a questionnaire was administered to 200 women in the preconception and conception periods in Toronto, Canada. Analyses revealed that lead and parabens were the most recognized EDCs, while triclosan and perchloroethylene were the least known. Greater knowledge of lead, parabens, bisphenol A, and phthalates significantly predicted chemical avoidance in PCHPs. Higher risk perceptions of parabens and phthalates also predicted greater avoidance. Women with higher education and chemical sensitivities were more likely to avoid lead. These findings support the need for targeted education to improve awareness to reduce EDC exposure—especially among women.